Factors that affect girls’ dropping out of secondary-level education: A case study of a village in Bangladesh - Ety Rani; Wardatul Akmam (Universitas Airlangga, 2023)
Knowing the factors affecting girls’ dropping out is very important. In spite of stipends, free schoolbooks and other incentives given by the government, girls’ dropout rate at the secondary level is not decreasing as expected in Bangladesh. The key objective of this study is to find out the different factors that affect girls’ dropout. The respondents of this research were girls who were 14-30 years old and had dropped out of the secondary level. In this study, the research area was Bharsho village in Naogaon district, Bangladesh. Using the case study method, data for this study were collected from 21-03-2019 to 05-04-2019 from 12 respondents through face-to-face communication, with the help of an unstructured interview schedule. Findings show that several factors are responsible for girls’ dropout. These are–early marriage, poverty, pregnancy, distance from home to school, eve-teasing, teachers’ maltreatment, negative attitude of society towards girls’ acquisition of education, poor academic performance, lack of security and the notion that if a daughter is more educated, it will cause greater difficulty in getting an equally qualified husband. Among these factors, early marriage is the most prominent.